Circulating oxylipin and bile acid profiles of dexmedetomidine, propofol, sevoflurane, and S-ketamine : a randomised controlled trial using tandem mass spectrometry - Nummela Aleksi; Laaksonen Lauri; Scheinin Annalotta; Kaisti Kaike; Vahlberg Tero; Neuvonen Mikko; Valli Katja; Revonsuo Antti; Perola Markus; Niemi Mikko; Scheinin Harry; Laitio Timo (Elsevier, 2025)
Background: This exploratory study aimed to investigate whether dexmedetomidine, propofol, sevoflurane, and S-ketamine affect oxylipins and bile acids, which are functionally diverse molecules with possible connections to cellular bioenergetics, immune modulation, and organ protection.
Methods: In this randomised, open-label, controlled, parallel group, Phase IV clinical drug trial, healthy male subjects (n=160) received equipotent doses (EC50 for verbal command) of dexmedetomidine (1.5 ng ml-1; n=40), propofol (1.7 μg ml-1; n=40), sevoflurane (0.9% end-tidal; n=40), S-ketamine (0.75 μg ml-1; n=20), or placebo (n=20). Blood samples for tandem mass spectrometry were obtained at baseline, after study drug administration at 60 and 130 min from baseline; 40 metabolites were analysed.
Results: Statistically significant changes vs placebo were observed in 62.5%, 12.5%, 5.0%, and 2.5% of analytes in dexmedetomidine, propofol, sevoflurane, and S-ketamine groups, respectively. Data are presented as standard deviation score, 95% confidence interval, and P-value. Dexmedetomidine induced wide-ranging decreases in oxylipins and bile acids. Amongst others, 9,10-dihydroxyoctadecenoic acid (DiHOME) -1.19 (-1.6; -0.78), P<0.001 and 12,13-DiHOME -1.22 (-1.66; -0.77), P<0.001 were affected. Propofol elevated 9,10-DiHOME 2.29 (1.62; 2.96), P<0.001 and 12,13-DiHOME 2.13 (1.42; 2.84), P<0.001. Analytes were mostly unaffected by S-ketamine. Sevoflurane decreased tauroursodeoxycholic acid (TUDCA) -2.7 (-3.84; -1.55), P=0.015.
Conclusions: Dexmedetomidine-induced oxylipin alterations may be connected to pathways associated with organ protection. In contrast to dexmedetomidine, propofol emulsion elevated DiHOMEs, oxylipins associated with acute respiratory distress syndrome, and mitochondrial dysfunction in high concentrations. Further research is needed to establish the behaviour of DIHOMEs during prolonged propofol/dexmedetomidine infusions and to verify the sevoflurane-induced reduction in TUDCA, a suggested neuroprotective agent.
Clinical trial registration NCT02624401.